Can Ixodes trianguliceps sustain a transmission cycle of tick-borne encephalitis virus? - Sprong, Hein; Holding, Maya L.; Brila, Ilze; Cayol, Claire; de Vries, Ankje; Henttonen, Heikki; Koskela, Esa; Mappes, Tapio; Sipari, Saana; Kallio, Eva R. (Elsevier, 2025)
The transmission dynamics of the tick-borne encephalitis virus (TBEV) remain enigmatic. New lineages of the European TBEV-variant have been emerging in areas where it was not expected to circulate, questioning their origins. Although Ixodes ricinus and I. persulcatus are primary vectors for TBEV, other tick species have also been proposed to transmit the virus. Under natural conditions, I. trianguliceps can maintain Anaplasma phagocytophilum and Babesia microti circulation, but not Borrelia burgdorferi sensu lato. As I. trianguliceps is reported to be a vector for TBEV, we investigated whether it can sustain a cryptic TBEV transmission in areas without I. ricinus and/or I. persulcatus. Sera from 951 bank voles from six sites in Finland, where I. trianguliceps, but neither I. ricinus nor I. persulcatus, have been observed, were negative for TBEV antibodies, and B. burgdorferi s.l., but positive for A. phagocytophilum and B. microti. In contrast, 32 bank voles from two endemic TBEV-foci, where I. ricinus/I. persulcatus are abundant, were positive for TBEV-antibodies as well as B. burgdorferi s.l., A. phagocytophilum and B. microti. Our results provide no evidence that TBEV would circulate alone by I. trianguliceps under natural conditions. Our results corroborate previous findings that A. phagocytophilum and B. microti, but neither TBEV nor B. burgdorferi s.l., can be sustained in the absence of I. ricinus/I. persulcatus. Whether TBEV can circulate in cryptic cycles or whether I. trianguliceps contributes to the maintenance of TBEV in the rodent - tick cycle, remains unresolved, but warrants further investigations.
Keywords: Ixodes ricinus; Ixodes persulcatus; Ixodes trianguliceps; tick-borne encephalitis virus; Clethrionomys glareolus; transmission dynamics